Cerebral Adaptation Associated with Peripheral Nerve Recovery in Neuralgic Amyotrophy: A Randomized Controlled Trial. (January 2023) - Lustenhouwer, Renee; Cameron, Ian G.M.; van Alfen, Nens; Toni, Ivan; Geurts, Alexander C.H.; van Engelen, Baziel G.M.; Groothuis, Jan T.; Helmich, Rick C.
Background: Neuralgic amyotrophy (NA) is a common peripheral nerve disorder caused by auto-immune inflammation of nerves in the brachial plexus territory, characterized by acute pain and weakness of the shoulder muscles, followed by motor impairment. Recent work has confirmed that NA patients with residual motor dysfunction have abnormal cerebral sensorimotor representations of their affected upper extremity. Objective: To determine whether abnormal cerebral sensorimotor representations associated with NA can be altered by specialized, multidisciplinary outpatient rehabilitation focused on relearning motor control. Methods: 27 NA patients with residual lateralized symptoms in the right upper extremity participated in a randomized controlled trial, comparing 17 weeks of multidisciplinary rehabilitation ( n = 16) to usual care ( n = 11). We used task-based functional MRI and a hand laterality judgment task, which involves motor imagery and is sensitive to altered cerebral sensorimotor representations of the upper extremity. Results: Change in task performance and related brain activity did not differ significantly between the multidisciplinary rehabilitation and usual care groups, whereas the multidisciplinary rehabilitation group showed significantly greater clinical improvement on the Shoulder Rating Questionnaire. Both groups, however, showed a significant improvement in task performance from baseline to follow-up, and significantly increased activity in visuomotor occipito-parietal brain areas, both specific to their affected upper extremity. Conclusions: Abnormal cerebral sensorimotor representations of the upper extremity after peripheral nerve damage in NA can recover toward normality. As adaptations occurred in visuomotor brain areas, multidisciplinary rehabilitation after peripheral nerve damage may be further optimized by applying visuomotor strategies. This study is registered at ClinicalTrials.gov (NCT03441347).